The Relationship of Experience, Motivation, and Workload to the Performance of Nurses in the Operating Room - Benny Chandra; Aprina, Aprina; Sunarsih, Sunarsih; Kodri, Kodri (Jurnal Kesehatan, 2025)
Performance is a measurable, both quantitative and qualitative, outcome for nurses who fulfill their responsibilities in providing patient care in accordance with their professional duties. This study aimed to determine the relationships among work experience, motivation, and workload and nurses' performance in the operating room at Urip Sumoharjo Hospital, Lampung Province, in 2024. The research used a quantitative design with a cross-sectional approach, conducted from March to April 2024. The population consisted of 37 nurses, all included as respondents through a total sampling technique. Data were collected using structured questionnaires completed by respondents and analyzed using univariate and bivariate analyses with the Chi-square test. The results showed that 28 nurses (75.7%) demonstrated good performance, supported by adequate work experience in 23 (62.2%), high motivation in 24 (64.9%), and a low workload in 27 (73.0%). Statistical analysis revealed significant relationships between experience (p=0.004), motivation (p=0.002), and workload (p=0.000) with nurse performance (p<0.05). The study concludes that work experience, motivation, and workload significantly influence nurses' performance in the surgical unit at Urip Sumoharjo Hospital. It is recommended that hospital management pay greater attention to enhancing nurse motivation and managing workloads to improve the quality of nursing services provided to patients.